Rouviere’s Sulcus: An Important Anatomical Landmark in Laparoscopic Cholecystectomy - Bhattarai, Suraj Raj; Acharya, Poonam; Yadav, Prabin Kumar; Rajbhandari, Paras (Journal of Nepalgunj Medical College, 2022)
Introduction: Though laparoscopic cholecystectomy is a gold standard treatment for symptomatic cholelithiasis, safe dissection of Calot’s triangle is important to avoid major complications like injury to bile duct, vessels and nearby organs. Aims: This study was designed to determine the frequency, description of Rouviere’s sulcus and its role in safe laparoscopic cholecystectomy. Methods:This prospective cross-sectional study was conducted at the Department of Surgery, Karuna Hospital, Nepal from January 2022 to September 2022. Patients who underwent laparoscopic cholecystectomy, presence of Rouviere’s sulcus were identified and classified, kept in Group A and absent in Group B. If the common bile duct outline visualized, its relation with Rouviere’s sulcus was noted and used as reference point for gall bladder dissection. The perioperative complications, conversion to open procedure, operative time and hospital stay were recorded. Results: Among 100 patients, the Rouviere’s sulcus was present in 79% and absent in 21%. Type I is the most common (65.82%). It was found above the level of common bile duct line in 84.81%. Cystic artery injury was present in 1.26% (Group A) and 14.28% (Group B). Bile/stone spillage 1.26% (Group A) and 9.52% (Group B), port hematoma 2.52% (Group A) and 9.52% (Group B), operative time 43.17±8.57 minutes (Group A) and 61.29±12.07 minutes (Group B), conversion to open procedure was none in Group A and 9.52% (Group B) and hospital stay 1.23±0.59 days in group A and 3.16±1.16 days in Group B. Conclusion: Rouviere’s sulcus is an important extrabiliary anatomical landmark, seen in majority of patients for safe laparoscopic cholecystectomy.